Toward human uterus tissue engineering: Uterine decellularization in a non‐human primate species - Lucía De Miguel‐Gómez; Edina Sehic; Emy Thorén; Johan Ahlström; Hardis Rabe; Mihai Oltean; Mats Brännström; Mats Hellström (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Uterus bioengineering offers a potential treatment option for women with uterine factor infertility and for mitigating the risk of uterine rupture associated with women with defective uterine tissue. Decellularized uterine tissue scaffolds proved promising in further in vivo experiments in rodent and domestic species animal models. Variations in the extracellular matrix composition among different species and adaptations of the decellularization protocols make it difficult to compare the results between studies. Therefore, we assessed if our earlier developed sodium deoxycholate‐based decellularization protocol for the sheep and the cow uterus could become a standardized cross‐species protocol by assessing it on the non‐human primate (baboon) uterus. Material and Methods The baboon uterus was decellularized using sodium deoxycholate, and the remaining acellular scaffold was quantitatively assessed for DNA, protein, and specific extracellular matrix components. Furthermore, electron microscopy deepened morphology examination, while the chorioallantoic membrane assay examined the scaffolds' cytotoxicity, bioactivity, and angiogenic properties. The in vitro recellularization efficiency of the scaffolds using xenogeneic (rat) bone marrow‐derived mesenchymal stem cells was also assessed. Finally, the immune potential of the scaffolds was evaluated by in vitro exposure to human peripheral blood mononuclear cells. Results We obtained a decellularized baboon uterus with preserved extracellular matrix components by adding an 8‐h sodium deoxycholate perfusion to our previously developed protocol for the sheep and cow models. This minor modification resulted in scaffolds with less than 1% of immunogenic host DNA content while preserving important uterine‐specific collagen, elastin, and glycosaminoglycan structures. The chorioallantoic membrane assay and in vitro recellularization experiments confirmed that the scaffolds were bioactive and non‐cytotoxic. As we have observed in other animal models, the enzymatic scaffold preconditioning with matrix metalloproteinases improved the recellularization efficiency further. Additionally, the preconditioning generated more immune‐privileged scaffolds, as shown in a novel in vitro co‐culture assay with human peripheral blood mononuclear cells. Conclusions For the first time, our data demonstrate the efficiency of our protocol for non‐human primate uteri and its translational potential. This standardized protocol will facilitate cross‐study comparisons and expedite clinical translation.